Fear of Crime among Women in the Old City Center of Istanbul - Yirmibesoglu, Funda; Ergun, Nilgun (Scientific Research Publishing, Inc., 2015)
Istanbul, the biggest city of Turkey with a population of 17 million people, is a city where both the negative and positive effects of urban life standards are intensely experienced. Along with problems such as migration from rural areas to urban areas, rapid population growth, unemployment and squatting, crime rates have recently been observed to go higher (Yirmibesoglu & Ergun, 2013). The old city center, Beyoglu was infamously known for its high crime rates and fear of crime, but today it seems that this image has changed and the fear of crime has decreased. Among the reasons for this decrease, we can mention the fact that Beyoglu has been through a gentrification process that some buildings have been restored, and that urban design implementations have been done in some streets. This study aimed to find out how fear of crime according to gender differed before and after the renovation process. With this aim in mind, field research and surveys were conducted in 2006 and 2010. The research problem, fear of crime and environmental safety in Beyoglu, was investigated based on certain variables such as the participants’ gender, occupation, duration of residence in Istanbul, the place of residence, age group, place of birth, and educational level; the participants were also asked about the frequency of their visits to Beyoglu and the reasons why they go to Beyoglu. The results of the study revealed the differences in fear of crime between men and women. It was found that Beyoglu district became safer after the renovations; yet, the rate of fear of walking alone, and therefore the fear of crime, was found to be higher among women than among men.